2020
DOI: 10.1101/2020.09.22.309260
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two Regulators of G-protein signaling (RGS) proteins FlbA1 and FlbA2 differentially regulate fumonisin B1 biosynthesis in Fusarium verticillioides

Abstract: Fumonisins are a group of mycotoxins produced by maize pathogen Fusarium verticillioides that pose health concerns to humans and animals. Yet we still lack a clear understanding of the mechanism of fumonisins regulation during pathogenesis. The heterotrimeric G protein complex, which consists of Gα, Gβ, and Gγ subunits, plays an important role in transducing signals under environmental stress. Furthermore, regulators of G-protein signaling (RGS) proteins act as negative regulators in heterotrimeric G protein s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, it has been suggested that regulators of G protein (RGS)/Gα i interactions promote trafficking and clearance of aged neutrophils. 155 Similarly, following exposure to phosphatidylserine and oxidative stress, aging glycated erythrocytes are engulfed by EC, thereby fostering atherothrombotic events. 156 More recently, models of extreme trajectories of vascular aging have been described, ranging from early vascular aging with premature cell senescence, to later, supernormal vascular aging characterized by delayed cell senescence.…”
Section: From Arterial Wall Clearance Functions To Pathologymentioning
confidence: 99%
“…However, it has been suggested that regulators of G protein (RGS)/Gα i interactions promote trafficking and clearance of aged neutrophils. 155 Similarly, following exposure to phosphatidylserine and oxidative stress, aging glycated erythrocytes are engulfed by EC, thereby fostering atherothrombotic events. 156 More recently, models of extreme trajectories of vascular aging have been described, ranging from early vascular aging with premature cell senescence, to later, supernormal vascular aging characterized by delayed cell senescence.…”
Section: From Arterial Wall Clearance Functions To Pathologymentioning
confidence: 99%